Effects of the interactions between glutaraldehyde and the polymeric matrix on the efficacy of the biocide against pseudomonas fluorescens biofilms - Pereira, Maria Olívia (2001)
Glutaraldehyde (GTA) is a widely used biocide due to its high effectiveness. The experimental work reported here was carried out to assess the effectiveness of GTA in controlling biofilms formed by Pseudomonas fluorescens on stainless steel slides, and to compare efficacy against both planktonic and sessile microrganisms. The tests were performed using two concentrations of GTA (50 and 100mg L-1), biofilms of two ages (7 and 15 d), several pH values (5, 7 and 9) and a range of exposure times (from 0 (control) to 1, 3, 7 and 24 h). The action of GTA on biofilm and planktonic populations was assessed by means of activity tests, zeta potential, and the wet weight of the biofilms. Biofilms were not completely removed after treatment with GTA in any of the conditions studied. The higher GTA concentration was more effective in reducing the bacterial activity of the biofilm. The biocide proved to be more effective for longer exposure times. GTA showed good antimicrobial activity against P. fluorescens in suspension, with higher activity at pH 9. The findings of this study suggest that when GTA is used to control biofilms, it reacts with one of the components of the matrix, the proteins, thereby reducing its antimicrobial action.